Development and Clinical Validation of a Potential Penside Colorimetric Loop-Mediated Isothermal Amplification Assay of Porcine Circovirus Type 3 - Zhang, Jie; Li, Miaomiao; Ou, Yunwen; Chen, Danian; Ding, Yaozhong; Zhang, Weibing; Li, Yanjun; Hou, Qian; Li, Xiaoyun; Zhou, Luoyi; Podgorska, Katarzyna; Zaberezhny, Alexei D.; et al. (Frontiers in Microbiology, 2022)
Porcine circovirus type 3 (PCV3), a novel circovirus, imposes great burdens on the global pig industry. The penside tests for detecting PCV3 are critical for assessing the epidemiological status and adjusting disease prevention in the context of no vaccine available. A one-step molecular assay based on visual loop-mediated isothermal amplification (vLAMP) was developed for simple and rapid detection of PCV3. We compared its sensitivity and specificity with TaqMan quantitative real-time polymerase chain reaction (qPCR) and applied the developed assay in the epidemiological study of 407 pooled swine sera collected in the whole China mainland during 2017-2018. We also explored the feasibility of the vLAMP assay for detecting crude samples without a prior DNA isolation step to expand its application field. Results showed that the vLAMP assay reliably detected PCV3 cap with a equal 10 DNA copies detection limit compared to that of Taqman qPCR assay. In the epidemiological study, the PCV3 positive detection rate for 407 swine pooled sera detected by the vLAMP assay was 37.35% (152/407) while it was 39.01% (159/407) for Taqman qPCR. For the direct-detection method, the results kept perfect specificity (100%) but displayed lower sensitivity (100% for CT<32), indicating the method not suited discrimination of low viral loads samples. The one-step vLAMP is a convenient, rapid, and cost-effective diagnostic validation procedure on penside and will enable epidemiological surveillance of PCV3 which has widely spread in China mainland.